Absence of dense platelet granules and ceroid-laden macrophages: Investigating the diversity of clinical presentations in Hermansky-Pudlak syndrome - Lanny T. DiFranza; Dong Chen; Charles C. Marboe; Alex J. Rai (Elsevier, 2021)
Hermansky-Pudlak syndrome (HPS) is an autosomal recessive genetic disorder in which the proper function of lysosome-related organelles (LROS) is impaired due to mutation in one of several well-characterized genes, including, but not limited to: HPS1, HPS3, and HPS4. Clinical manifestations include oculocutaneous albinism, nystagmus, platelet dysfunction, progressive pulmonary fibrosis, and granulomatous colitis. We present a case of a 28-year-old woman of Puerto Rican descent who required post-partum lung transplantation due to an inherited HPS1 mutation. The pathologies observed in HPS underline the mechanistic importance of LROS in a variety of tissue types and organ systems.